Effectiveness and safety of vernakalant vs flecainide for cardioversion of atrial fibrillation in the emergency department: the VERITA study - Giuseppe Dominijanni; Antonio F. Caballero-Bermejo; Ana Sainz-Herrero; Álvaro Pineda-Torcuato; Rosa Capilla-Pueyo; Belén Ruiz-Antorán (International Journal of Emergency Medicine)
Abstract Background Vernakalant is authorized in several countries, except in the U.S., where the FDA denied its commercialization due to safety concerns, generating debate about its use. Objective To compare the effectiveness and safety of intravenous (iv) vernakalant and iv flecainide in the conversion of atrial fibrillation (AF) to sinus rhythm (SR) in a hospital emergency department (ED). Design, settings and participants A retrospective observational study was conducted, including all AF episodes treated with vernakalant or iv flecainide in the ED between January 2012 and December 2022. Clinical characteristics of each episode were analyzed following routine clinical practice. Outcomes measure and analysis The primary outcome was the percentage of episodes achieving conversion to sinus rhythm during the emergency department stay. Secondary outcomes included clinical evolution, emergency department re-presentations, and outpatient cardiology consultations recorded over a 6-month period. Subgroup analyses evaluated the effectiveness of vernakalant and flecainide by age, sex, treatment timing, heart failure history, previous atrial fibrillation episodes, AF type, and CHADS-VAS score. Main findings A total of 289 patients and 414 AF episodes were included, with 151 treated with flecainide and 263 with vernakalant. The median age was 62 years, and 57.5% were male. Vernakalant converted 76.4% of episodes to SR during the ED stay, compared to 69.5% with flecainide (p = 0.124). AF recurrence at six months was lower in the vernakalant group (20.1% vs. 29.1%; p = 0.043), with fewer ED visits for recurrent AF (0.24 vs. 0.48; p = 0.001). Vernakalant was more effective in early treatment (< 12 h after symptom onset) (82.2% vs. 70.7%; p = 0.014) and in AF with rapid ventricular response (78.1% vs. 68.0%; p = 0.044). Both drugs were well tolerated, although flecainide was associated with higher rates of bradycardia, dizziness, and hypotension. Conclusions Vernakalant and flecainide demonstrated similar effectiveness and safety; however, vernakalant showed superior effectiveness in early treatment, faster conversion to SR, lower AF recurrence rates, and fewer ED visits within six months.